Induction of mitochondrial apoptotic pathway in triple negative breast carcinoma cells by methylglyoxal via generation of reactive oxygen species. Issue 9 (22nd May 2017) - Roy, Anirban; Ahir, Manisha; Bhattacharya, Saurav; Parida, Pravat Kumar; Adhikary, Arghya; Jana, Kuladip; Ray, Manju
Abstract : Triple negative breast cancer (TNBC) tends to form aggressive tumors associated with high mortality and morbidity which urge the need for development of new therapeutic strategies. Recently, the normal metabolite Methylglyoxal (MG) has been documented for its anti‐proliferative activity against human breast cancer. However, the mode of action of MG against TNBC remains open to question. In our study, we investigated the anticancer activity of MG in MDA MB 231 and 4T1 TNBC cell lines and elucidated the underlying mechanisms. MG dose‐dependently caused cell death, induced apoptosis, and generated ROS in both the TNBC cell lines. Furthermore, such effects were attenuated in presence of ROS scavenger N‐Acetyl cysteine. MG triggered mitochondrial cytochrome c release in the cytosol and up‐regulated Bax while down‐regulated anti‐apoptotic protein Bcl‐2. Additionally, MG treatment down‐regulated phospho‐akt and inhibited the nuclear translocation of the p65 subunit of NF‐κB. MG exhibited a tumor suppressive effect in BALB/c mouse 4T1 breast tumor model as well. The cytotoxic effect was studied using MTT assay. Apoptosis, ROS generation, and mitochondrial dysfunction was evaluated by flow cytometry as well as fluorescence microscopy. Western blot assay was performed to analyze proteins responsible for apoptosis. This study demonstrated MG as a potent anticancer agent against TNBC both in vitro and in vivo. The findings will furnish fresh insights into the treatment of this subgroup of breast cancer.